Proton pump inhibitor therapy after transcatheter angiography in refractory nonvariceal acute upper gastrointestinal bleeding patients: a cohort study - Xiao, X; Liu, X; Yan, H; Xing, X; Luo, X; Yang, J (BioMed Central, 2024)
Background: Transcatheter angiography (TA) could help to diagnose and treat refractory nonvariceal upper gastrointestinal bleeding (NVUGIB). Proton pump inhibitors (PPIs) are the key medication for reducing the rebleeding rate and mortality and are usually continued after TA. It is unknown whether high-dose PPIs after TA are more effective than the standard regimen. Methods: We retrospectively collected data from patients who received TA because of refractory NVUGIB from 2010 to 2020 at West China Hospital. 244 patients were included and divided into two groups based on the first 3 days of PPIs treatment. All baseline characteristics were balanced using the inverse probability of treatment weighting method. The 30-day all-cause mortality, rebleeding rate and other outcomes were compared. The propensity score matching method was also used to verify the results. Results: There were 86 patients in the high-dose group and 158 in the standard group. The average daily doses of PPI were 192.1 ± 17.9 mg and 77.8 ± 32.0 mg, respectively. Cox regression analysis showed no difference in the 30-day all-cause mortality (aHR 1.464, 95% CI 0.829 to 2.584) or rebleeding rate (aHR 1.020, 95% CI 0.693 to 1.501). There were no differences found in red blood cell transfusion, hospital stay length and further interventions, including endoscopy, repeating TA, surgery and ICU admission. The results were consistent in the subgroup analysis of patients with transcatheter arterial embolization. Conclusion: In refractory NVUGIB patients who received TA, regardless of whether embolization was performed, high-dose PPI treatment did not provide additional benefits compared with the standard regimen.